COMPLIANCE TO INTERNATIONAL TRADE RULES: THE CASE OF MALAYSIA’S ENVIRONMENTAL PROTECTION MEASURES (UUM Journal of Legal Studies, 2020)
An environmental protection measure will have an effect on international trade when it affects market access of goods and services. The objectives of this paper are to explore the international trade rules that need to be complied by the government of Malaysia with respect to invoking environmental protection measures and secondly, to look into the government’s compliance with international trade rules when invoking such measures. The international trade rules that need to be complied in this study are the World Trade Organization (WTO) agreements and the General Agreement on Tariffs and Trade (GATT). Malaysia’s environmental protection measures can be found in Malaysia’s domestic laws such as the Plant Quarantine Act 1976, Food Act 1983, Fisheries Act 1985 and national policies. The methodology employed in this study was by analyzing WTO and GATT agreements and decisions by the Dispute Settlement Bodies of the WTO in international dispute cases and also by analyzing Malaysia’s regulations in order to find out how far the government has complied with these international trade rules. The significance of this study is to recognize Malaysia’s efforts in dealing with international trade rules when invoking environmental protection measures.